IMPACTO DE LAS REMESAS INTERNACIONALES EN EL CRECIMIENTO ECONÓMICO: UN ESTUDIO DE CASO EN PAKISTAN (1975-2016) - Tariq, Bilal; Shabbir, Muhammad; Ahmed, Zeeshan; Tahir, Muhammad; Ahmed, Bilal; Saleem, Qasim; Ahsan, Muhammad (Revista Inclusiones, 2018)
The inflows of income through international remittances are an important source of economic growth and development in Pakistan. In 2015-2016, Pakistan got 20.1 billion as international remittances. To investigate the impact of international remittances on economic growth, it is necessary to grasp the different theories of remittances and migration. The elaborations in the theoretical and conceptual framework, thus recognize the problems, why or how certain relationships exist, and also explain the direction and the nature of the relationships among the variables. The study employed ad-hoc model to check the practical association between international remittances and economic growth in the Pakistan from the time period of 1975 to 2016. Therefore, we started our research work by the following functional form to determine the relationship between economic growth, personal remittances, GFCF and foreign direct investment.